Modern Challenges in Islamic Practice: The Role of Morality and Ethics - Nur, Faisal Muhammad (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
This study examines the need and processes for reform in Islamic thought amid contemporary challenges. Despite the eternal nature of Sharia, acknowledged by Allah, the conditions of modernity necessitate continuous ijtihad—dynamic interpretation—to preserve the relevance of Islamic teachings. This research employs a textual historical approach, focusing on the discourse of prominent scholars to understand the evolving nature of morality and ethics within Islamic traditions. The study underscores the critical role of ijtihad in addressing the ethical dilemmas posed by modern social changes, technological advancements, and the influence of authoritative religious interpretations. Therefore, an adaptive ethical framework that integrates both individual and collective moral values is essential to ensure that Islamic thought remains relevant and responsive to the complexities of a global society. This study advocates for a balanced approach to religious practices that align with contemporary moral and ethical standards, thereby supporting the sustainability and purity of Islamic teachings in a modern context.